2020
DOI: 10.1097/cm9.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

High salt-induced weakness of anti-oxidative function of natriuretic peptide receptor-C and podocyte damage in the kidneys of Dahl rats

Abstract: Background: Atrial natriuretic peptide (ANP) and its natriuretic peptide receptors A (NPR-A) and C (NPR-C) are involved in the regulation of physiological and pathophysiological process of blood pressure. The present study aimed to determine the role of NPR-C in the development of salt-sensitive hypertension. Methods: The Dahl salt-sensitive (DS) and salt-resistant (DR) rats were used in this study. Animals were matched according to their age and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The urine volume, pH and specific gravity of rats were not significantly different between the treatment groups. The rat's urine volume, pH and specific gravity values were significantly influenced from the treatments which were in agreement with the other studies [11][12][13][14][15][16][17]. The results of urine biochemical analysis of the rats are shown in Table 2.…”
Section: Urine and Feces Parameterssupporting
confidence: 90%
“…The urine volume, pH and specific gravity of rats were not significantly different between the treatment groups. The rat's urine volume, pH and specific gravity values were significantly influenced from the treatments which were in agreement with the other studies [11][12][13][14][15][16][17]. The results of urine biochemical analysis of the rats are shown in Table 2.…”
Section: Urine and Feces Parameterssupporting
confidence: 90%
“…[ 22 ] Peripheral molecular clocks are involved in the regulation of circadian blood pressure, as well as sodium and potassium homeostasis by kidneys. [ 23 , 24 ] Early researches have reported that the excretion of sodium, potassium, and water by renal metabolism followed a strong circadian pattern in both humans and non-human primates, independently of the time of day when food and water were ingested. [ 20 , 25 ] This study verified this circadian rhythm of urinary excretion in healthy adults, which might help improve the prediction formulas for 24-h urinary sodium excretion using single spot urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might be linked to the observed decrease in antioxidant enzymes activity vis-a-vis catalase and glutathione (GSH) in HSD-treated animals. Depleted level of GSH can be caused by increased generation of ROS, resulting in a buoyed level of malondialdehyde, TNF-α, interleukin-6 (IL-6), and deranged functioning of the immune system [46,47,48,49]. HSD also up-regulates inflammatory molecules like vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule1 (ICAM-1), and nuclear factor-kappa B (NF-κB) [46].…”
Section: Discussionmentioning
confidence: 99%